2019
DOI: 10.1080/13557858.2019.1606162
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of UK African-Caribbean prostate cancer survivors of discharge to primary care

Abstract: Black men are three times more likely to develop prostate cancer (PCa), to do so at a younger age and to experience a more aggressive form than White men. This study aims to understand the experiences of African-Caribbean men with respect to their discharge to primary care following successful PCa treatment and the challenges associated with survivorship. Design: Eight African-Caribbean men, who had been successfully treated for PCa, were recruited through the charity BME Cancer Communities. They participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Men of these ethnic backgrounds are at a higher risk of developing prostate cancer and do so at a younger age, so they are likely to have particular needs. For example, a recent study (Margariti et al, 2019) found African Caribbean prostate cancer survivors believed that lack of knowledge among GPs about aspects of PCa that were of particular relevance to them was problematic. While our study did not seek to address the issue, it is known that gay men with PCa report low satisfaction with PCa health care (NHS, 2014), and studies have reported that particular sources of dissatisfaction include assumptions of heterosexuality, lack of interest and lack of appropriate knowledge among healthcare professionals (e.g.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Men of these ethnic backgrounds are at a higher risk of developing prostate cancer and do so at a younger age, so they are likely to have particular needs. For example, a recent study (Margariti et al, 2019) found African Caribbean prostate cancer survivors believed that lack of knowledge among GPs about aspects of PCa that were of particular relevance to them was problematic. While our study did not seek to address the issue, it is known that gay men with PCa report low satisfaction with PCa health care (NHS, 2014), and studies have reported that particular sources of dissatisfaction include assumptions of heterosexuality, lack of interest and lack of appropriate knowledge among healthcare professionals (e.g.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…“It's a little kind of, look , well you know I've cured you of the cancer so that's the big job , you know . ” ‐ Participant (Ettridge et al, 2017) I spent a bit more time with them ( hospital specialists ) and I explained more things in more depth so when I did not have the answers from GPs or I felt that I wasn't given enough information ( … ) because of the consultant's expertise who is specialised especially in erectile dysfunction , that was his speciality whereas you get a GP who looks at everything and they are not specialised in that particular area . ‐ Participant (Margariti et al, 2019)…”
Section: Resultsmentioning
confidence: 99%
“…In one study (Margariti et al, 2019), men discussed their need to conceal negative emotions from their immediate family, in order to present themselves as a role model for their children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater emphasis on individual patient issues, understanding and needs after prostate cancer care is needed where aftercare is tailored to the individual patient. Patients may have different aftercare preferences according to age, education, gender and culture (Huibertse et al, 2017; Margariti et al, 2019). We need to acknowledge that for a sub‐group of men, face‐to‐face traditional follow‐up in outpatient clinics will be the best form of aftercare for them.…”
Section: Discussionmentioning
confidence: 99%